Frequency of delirium and subsyndromal delirium in an adult acute hospital population. (December 2014) - Meagher, D.; O'Regan, N.; Ryan, D.; Connolly, W.; Boland, E.; O'Caoimhe, R.; Clare, J.; Mcfarland, J.; Tighe, S.; Leonard, M.; Adamis, D.; Trzepacz, P. T.; et al.
Abstract : Background: The frequency of full syndromal and subsyndromal delirium is understudied. Aims: We conducted a point prevalence study in a general hospital. Method: Possible delirium identified by testing for inattention was evaluated regarding delirium status (full/subsyndromal delirium) using categorical (Confusion Assessment Method (CAM), DSM-IV) and dimensional (Delirium Rating Scale-Revised-98 (DRS-R98) scores) methods. Results: In total 162 of 311 patients (52%) screened positive for inattention. Delirium was diagnosed in 55 patients (17.7%) using DSM-IV, 52 (16.7%) using CAM and 58 (18.6%) using DRS-R98⩾12 with concordance for 38 (12.2%) individuals. Subsyndromal delirium was identified in 24 patients (7.7%) using a DRS-R98 score of 7–11 and 41 (13.2%) using 2/4 CAM criteria. Subsyndromal delirium with inattention ( v. without) had greater disturbance of multiple delirium symptoms. Conclusions: The point prevalence of delirium and subsyndromal delirium was 25%. There was modest concordance between DRS-R98, DSM-IV and CAM delirium diagnoses. Inattention should be central to subsyndromal delirium definitions.